Rapid detection of drug-resistant Mycobacterium tuberculosis by Modified MODS assay suitable for resource-poor settings. - Bashir Ahamd Fomda; Gulnaz Bashir; Sehrish Baqal; Yaawar Bashir Mir; Rehana Ali; Altaf Hussain Khan; Asiya Khan; Anis Bashir; G M Chuloo (Public Library of Science (PLoS), 2024)
Background Cross contamination and biosafety are concerns with the microscopic observation drug susceptibility assay. To address these issues, we modified the MODS technique in the current study. Methodology/principal findings Two hundred and seventy-five samples were processed on LJ media and drug susceptibility was performed by the Indirect agar proportion method. A modified MODS test was done in tissue culture bottles. GenoType MTBDRplus assay was performed to detect the resistance and mutational pattern associated with the resistances. Sensitivity, specificity, positive predictive value, and negative predictive value for the detection of tuberculosis by modified MODS were 97.44%, 80.00%, 97.44%, and 80.00% respectively. The perfect agreement was seen between modified MODS and the Indirect agar proportion method for drug susceptibility testing of isoniazid (kappa = 0.923) and rifampicin (kappa = 1). The contamination rate, cost and TAT for modified MODS were less as compared to the solid media. In the case of MDR-TB isolates S531L (66.66%) was the most prevalent mutation in the rpoB gene followed by S315T2 mutation (58.33%) and T8C (41.66%) in katG and inhA gene respectively. In hetero-resistant strains, C-15T mutation (37.50%) was the most common followed by A-16G (12.50%) in the inhA gene. In INH mono-resistant strains only two mutations were observed i.e., S-315T1(50%) and C-15T (50%) in the katG and inhA genes respectively. Conclusions/significance Modified MODS proved to be cost-effective and user-friendly, with minimal risk to the handler and no cross-contamination between samples were observed. Hence, it can be used in low-income countries for early detection of tuberculosis and its resistance.